Label and production method of same
Patent Information
- Application Number
- JP2023133342
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0034】 本発明によれば、粘着剤層を備えるラベルのプローブタック試験における、前記粘着剤層の粘着面に押し当てたプローブの引き剥がしを開始した時点からプローブが粘着面から引き剥がされた時点までの時間(ms)を、プローブタック値のピーク値(g)で除算した指標値(ms/g)の平均値が、0.099以上0.106以下であるので、ラベルの剥離音を小さくすることができる一方、ラベルの経時的な接着力の上昇を抑制することができる。
Smart Images

Figure 2025028494000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a label and a manufacturing method thereof, and more particularly to a label suitable for a flap label or the like used for opening and closing the access opening of a package, and a manufacturing method thereof. [Background technology]
[0002] 2. Description of the Related Art Conventionally, various proposals have been made to reduce the crackling noise that occurs when an article having an adhesive portion is peeled off from an adherend (see, for example, Patent Document 1).
[0003] In particular, in the case of a flap label that opens and closes the dispensing opening of a bag-shaped package that stores wet tissues or the like, it is desirable to reduce the peeling noise because the label is repeatedly opened and closed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-55268 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the case of a product such as a package in which the opening for dispensing is opened and closed by a flap label as described above, the product may be stored for a long period of time.
[0006] Therefore, if the adhesive strength of the flap label increases significantly over time, the adhesive strength of the flap label may increase as the storage period becomes longer, making it difficult to open the package.
[0007] The present invention has been made in light of the above-mentioned circumstances, and aims to provide a label and a manufacturing method thereof that can reduce peeling noise and suppress an increase in adhesive strength over time. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the present inventors conducted intensive research and, as a result, by focusing on the time from when peeling of the probe pressed against the adhesive surface begins to the time when the probe is peeled off from the adhesive surface and the peak value of the probe tack value in a probe tack test, which measures the probe tack value when a probe pressed against an adhesive surface is peeled off, and using the value obtained by dividing the said time by the peak value as an index value, they discovered that it is possible to specify an adhesive that can reduce the peeling sound and suppress an increase in adhesive strength over time, and thus completed the present invention.
[0009] That is, the present invention is configured as follows.
[0010] (1) The label according to the present invention is a label having an adhesive layer, In a probe tack test in which a probe tack value is measured when a probe is pressed against the adhesive surface of the adhesive layer and then peeled off, the average index value (ms / g) obtained by dividing the time (ms) from the point at which peeling of the probe pressed against the adhesive surface begins to the point at which the probe is peeled off from the adhesive surface by the peak value (g) of the probe tack value is 0.099 or more and 0.106 or less.
[0011] Since the index value varies, the average of the index values is used instead of the index value itself. By specifying the average value, the influence of variation can be eliminated.
[0012] According to the label of the present invention, the average index value is 0.099 or more, so that the peeling sound can be reduced, while the average index value is 0.106 or less, so that the increase in adhesive strength over time can be suppressed.
[0013] The reason why the peeling sound can be reduced when the average index value is 0.099 or more, and the increase in adhesive strength over time can be suppressed when the average index value is 0.106 or less, is not clear, but can be thought of as follows.
[0014] When peeling a label from an object, if the adhesive is hard and not easily deformed, the peeling does not proceed smoothly, and it is presumed that peeling occurs repeatedly in small sections, resulting in a loud peeling noise known as zipping.
[0015] On the other hand, if the adhesive is soft and easily deformed, it is presumed that over time the adhesive will penetrate into minute irregularities on the surface of the adherend, increasing the adhesive strength.
[0016] Therefore, in order to reduce the peeling noise, it is preferable that the adhesive be soft and easily deformed, but in order to suppress an increase in adhesive strength over time, it is preferable that the adhesive be hard and difficult to deform.
[0017] That is, in order to reduce the peeling noise and to suppress an increase in adhesive strength over time, the adhesive needs to be appropriately soft and hard.
[0018] If there is an index that can specify such an adhesive that is appropriately soft and hard, it will be easy to obtain an adhesive that is appropriately soft and hard based on that index.
[0019] The present inventors discovered that an effective indicator value for this purpose is the value obtained by dividing the time from when peeling off the probe pressed against the adhesive surface in a probe tack test begins to when the probe is peeled off from the adhesive surface, by the peak probe tack value, as described above, and completed the present invention.
[0020] In a probe tack test, the time from when peeling off the probe pressed against the adhesive surface begins to the time when the probe is peeled off from the adhesive surface is the time during which the adhesive adhering to the probe is stretched and deformed by the peeling off of the probe, and can be called the deformation time.
[0021] It is believed that if the deformation time is short, the adhesive is difficult to deform and is hard, and conversely, if the deformation time is long, the adhesive is easy to deform and is soft.
[0022] However, this deformation time varies not only with the hardness or softness of the adhesive, but also with the adhesive strength of the adhesive. If the adhesive strength is strong, the deformation time tends to be long, and if the adhesive strength is weak, the deformation time tends to be short.
[0023] Therefore, in order to reduce the effect of the strength of adhesive strength on the deformation time, the deformation time is divided by the peak probe tack value corresponding to the strength of adhesive strength to obtain an index value for determining whether the adhesive is hard or soft.
[0024] Since the probe tack value and deformation time of the probe tack test vary, the index value, which is the value obtained by dividing the deformation time by the peak value of the probe tack value, also varies. Therefore, the influence of the variation is eliminated by using the average value of the index value instead of the index value itself.
[0025] By setting the average value of this index to be 0.099 or more and 0.106 or less, a suitably soft and hard adhesive is obtained, which, as described below, makes it possible to reduce the sound of peeling the label and suppress the increase in adhesive strength over time.
[0026] (2) A method for producing a label according to the present invention is a method for producing a label including a substrate and an adhesive layer, a blending step of blending a first pressure-sensitive adhesive and a second pressure-sensitive adhesive, and a pressure-sensitive adhesive layer forming step of forming a pressure-sensitive adhesive layer made of the pressure-sensitive adhesives blended in the blending step on one surface of the base material, In a probe tack test in which a probe tack value is measured when a probe is pressed against the adhesive surface of the formed adhesive layer and then peeled off, the average index value (ms / g) obtained by dividing the time (ms) from the point at which peeling of the probe pressed against the adhesive surface begins to the point at which the probe is peeled off by the peak value (g) of the probe tack value is 0.099 or more and 0.106 or less.
[0027] According to the label manufacturing method of the present invention, in a probe tack test in which a probe is pressed against the adhesive surface of an adhesive layer made of an adhesive that is a blend of a first adhesive and a second adhesive and then peeled off to measure the probe tack value, the average index value (ms / g) obtained by dividing the time (ms) from the point at which peeling of the probe pressed against the adhesive surface begins to the point at which the probe is peeled off from the adhesive surface by the peak value (g) of the probe tack value is 0.099 or more and 0.106 or less, so that the peeling sound of a label having an adhesive layer that is a blend of a first adhesive and a second adhesive can be reduced and an increase in adhesive strength over time can be suppressed.
[0028] (3) In one embodiment of the present invention, the first adhesive has an average index value of less than 0.099 in the probe tack test of a first adhesive layer made of the first adhesive, and the second adhesive has an average index value of more than 0.106 in the probe tack test of a second adhesive layer made of the second adhesive.
[0029] In this embodiment, the first adhesive has an average index value less than 0.099, and the second adhesive has an average index value greater than 0.106. Therefore, by selecting the blending ratio of the two adhesives, a label can be obtained having an adhesive layer with an average index value between 0.099 and 0.106.
[0030] (4) In another embodiment of the present invention, in the blending step, the first pressure-sensitive adhesive and the second pressure-sensitive adhesive are blended in a mass ratio of 30:70 to 10:90.
[0031] According to this embodiment, by mixing the first adhesive and the second adhesive so that the mass ratio is between 30:70 and 10:90, a label can be obtained having an adhesive layer in which the average value of the index is 0.099 or more and 0.106 or less.
[0032] (5) In yet another embodiment of the present invention, the first adhesive has an adhesive strength of 1.52 to 1.78 (N / 10 mm), a holding strength, a slippage after 1440 minutes (24 hours) of 0 to 0.02 mm, and a ball tack of No. 12 to 14, and the second adhesive has an adhesive strength of 0.64 to 0.79 (N / 10 mm), a holding strength, a slippage after 1440 minutes (24 hours) of 0.02 to 0.06 mm, and a ball tack of No. 12 to 14.
[0033] According to this embodiment, by blending first and second adhesives having three adhesive properties, namely, adhesive strength (adhesive strength), holding power and ball tack (tack), within a predetermined range, a label can be obtained having an adhesive layer in which the average value of the index values is 0.099 or more and 0.106 or less. Effect of the Invention
[0034] According to the present invention, in a probe tack test of a label having an adhesive layer, the average index value (ms / g) obtained by dividing the time (ms) from the point at which peeling of a probe pressed against the adhesive surface of the adhesive layer begins to the point at which the probe is peeled off from the adhesive surface by the peak probe tack value (g) is 0.099 or more and 0.106 or less, so that the peeling sound of the label can be reduced while the increase in adhesive strength of the label over time can be suppressed. [Brief description of the drawings]
[0035] [Figure 1] FIG. 1 is a schematic cross-sectional view of a label according to one embodiment of the present invention. [Diagram 2]FIG. 2 is a diagram showing a schematic diagram of the change in probe tack value over time in a probe tack test, corresponding to the positional relationship between the adhesive and the probe. [Diagram 3] FIG. 3 is a graph showing the relationship between the average deformation time / peak value, which is an index value obtained in the probe tack test, and the peeling sound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0037] FIG. 1 is a schematic cross-sectional view of a label according to one embodiment of the present invention.
[0038] The label 1 of this embodiment comprises a film-like surface substrate 2, an adhesive layer 3 provided on the back side of the surface substrate 2, and a release paper 4 provided on the back side of the adhesive layer 3. The surface substrate 2 comprises a base film 5 and a laminate layer 6.
[0039] The material of the base film 5 is not particularly limited, but is preferably a resin film such as a polyethylene terephthalate (PET) film, a polypropylene film, or a polyimide film, and in this embodiment, a PET film is used.
[0040] The material of the laminate layer 6 is, for example, a resin film such as a polypropylene film (PP).
[0041] The release paper 4 is a support such as paper or a resin film on which a release layer is formed, and is, for example, a polyethylene laminated release paper.
[0042] The adhesive of the adhesive layer 3 is, for example, an acrylic adhesive.
[0043] The present inventors have investigated two types of acrylic adhesives, a first adhesive and a second adhesive, in order to obtain a label that produces little peeling noise and is capable of suppressing an increase in adhesive strength over time.
[0044] First, the three adhesive properties of the first and second adhesives, that is, adhesive strength (adhesive strength), holding strength, and ball tack (tack), will be described.
[0045] The label samples used to measure the adhesive properties of the first and second adhesives had a surface substrate of a 50 μm transparent PET (polyethylene terephthalate) film with a 40 μm laminate layer of PP (polypropylene).
[0046] The label samples were prepared as follows: The first and second adhesives were applied to the release paper at 23±1 g / m using an applicator. 2 Each was coated and dried in a dryer at 105°C for 2 minutes. Then, the above-mentioned surface substrates were laminated together and the pressure was 10 kg / cm. 2 The molded product was prepared by pressing for 10 minutes at 40°C.
[0047] The adhesive properties were measured in accordance with JIS Z0237.
[0048] Regarding adhesive strength, a label sample was attached to a PET film used as a film packaging material with a 2 kg roller, and after 30 minutes, measurements were taken at a peel speed of 300 mm / min and a peel angle of 180°.
[0049] For the retention strength, a label sample was cut to 25mm wide x 75mm long, and attached to a SUS plate with an area of 25mm x 25mm. After 1 minute, a static load of 1kg was applied and the time it took for the sample to fall was measured. If the sample had not fallen after 24 hours (1440 minutes), the displacement (mm) was measured.
[0050] Regarding ball tack, a label sample 10 cm long was prepared based on JIS Z0237 and set in a ball tack measuring device with an inclination angle of 30°. The largest ball number that stopped when a ball was rolled on the adhesive surface from a run-up position of 10 cm was investigated. The ball numbers were 2 to 32, and the ball sizes were 2 / 32 to 32 / 32 inches. The stopping condition was a stop of 5 seconds. In the case of substrate destruction, the smallest ball number that destroyed the substrate was recorded.
[0051] Adhesion, holding power, and ball tack were each measured four times, and the results are shown in Table 1 below.
[0052] [Table 1] The adhesive properties of the first and second adhesives were defined based on the maximum and minimum values of the four measured values shown in Table 1, as shown in Table 2 below.
[0053] [Table 2] As shown in Table 2, the adhesive strength of the first adhesive is 1.52 to 1.78 (N / 10 mm), and the adhesive strength of the second adhesive is 0.64 to 0.79 (N / 10 mm).
[0054] The holding strength of the first adhesive is such that the displacement after 1440 minutes (24 hours) is 0 to 0.02 mm, and the holding strength of the second adhesive is such that the displacement after 1440 minutes (24 hours) is 0.02 to 0.06 mm.
[0055] The ball tack of each of the first and second adhesives is No.12 to No.4.
[0056] In the present invention, label samples were prepared in the same manner as above using the first and second adhesives, and a probe tack test was performed and the peeling sound was measured.
[0057] For comparison, label samples were made using the third and fourth adhesives, and the probe tack test was performed and the peeling noise was measured.Furthermore, the probe tack test was performed on label samples using commercially available adhesives from other companies, and the peeling noise was measured.
[0058] The label samples using the third and fourth adhesives, as well as the label samples using commercially available adhesives from other companies, all used a 50 μm transparent PET film with a 40 μm PP laminate layer formed on it as the surface substrate, just like the samples using the first and second adhesives described above.
[0059] In addition, the label samples using the third and fourth adhesives and the label samples using other companies' commercially available adhesives were coated with a coating weight of 23±1g / m using an applicator on the release paper, in the same way as the label samples using the first and second adhesives. 2 Then, the surface substrate is laminated and the coating is applied under a pressure of 10 kg / cm. 2 The molded product was prepared by pressing for 10 minutes at 40°C.
[0060] The measurement results of the adhesive properties of the third and fourth adhesives used for comparison and a commercially available adhesive are shown in Table 3 below.
[0061] [Table 3] As shown in Table 3, the adhesive strength of the third adhesive is 1.68 (N / 10 mm), the adhesive strength of the fourth adhesive is 7.93 (N / 10 mm), and the adhesive strength of the commercially available adhesive is 0.96 (N / 10 mm).
[0062] The holding power of the third adhesive is a displacement of 0.04 mm after 1440 minutes (24 hours), the holding power of the fourth adhesive is 70 minutes, and the holding power of the commercially available adhesive is 1192 minutes.
[0063] The ball tack of the third and fourth adhesives was No. 7, while the ball tack of the commercially available adhesive was No. 11.
[0064] A probe tack test was carried out on the label samples prepared as described above using the first to fourth adhesives and a commercially available adhesive. This probe tack test measures the probe tack value (force) when a cylindrical probe is brought into contact with the adhesive surface for a certain period of time and then peeled off.
[0065] FIG. 2 is a diagram for explaining this probe tack test, and is a diagram that shows a schematic diagram of the change in probe tack value over time in relation to the positional relationship between the pressure-sensitive adhesive and the probe.
[0066] The probe tack test was conducted using a stainless steel cylindrical probe with a diameter of 5 mm, in accordance with the standard ASTM D2979. The sample size was 15 mm x 15 mm, the contact load (pressing load) was 20 g, the peeling speed was 1 cm / min, and the contact time (pressing load holding time) was 1 sec.
[0067] As shown in Fig. 2, first, when the probe 8 is brought into contact with the adhesive 7 and a load of 20 g is applied, the probe tack value becomes negative. After a contact time of 1 sec has elapsed, the probe 8 is pulled downward to start peeling off the adhesive 7. This peeling causes the probe tack value to increase and eventually reach a peak value (maximum value).
[0068] Thereafter, the probe tack value decreases, and the adhesive 7 is pulled by the probe 8, increasing its downward extension, until the probe 8 is peeled off the adhesive 7, and the probe tack value becomes "0".
[0069] In this probe tack test, the inventors measured the peak value PV of the probe tack value, and also measured the time from the point t1 when the probe 8 was pulled downward to start peeling it off from the adhesive 7 to the point t2 when the probe 8 was peeled off from the adhesive 7 as the deformation time T during which the adhesive 7 was deformed by the pulling.
[0070] In this probe tack test, when attention is paid to the deformation time T, if the deformation time T is short, the adhesive tends to be hard and difficult to deform, and conversely, if the deformation time T is long, the adhesive tends to be soft and easy to deform.
[0071] However, if the adhesive strength of the adhesive is strong, the deformation time T tends to be long, and conversely, if the adhesive strength is weak, the deformation time T tends to be short.
[0072] Therefore, it is not possible to determine, based on the deformation time T alone, whether the adhesive is hard and difficult to deform, or soft and easy to deform.
[0073] Therefore, in order to eliminate the effect that the adhesive strength of the adhesive has on the deformation time T, the inventors divided the deformation time T by the peak value PV of the probe tack value, and used this value (T / PV) as an index value indicating whether the adhesive is hard and difficult to deform, or soft and easy to deform.
[0074] The inventors performed the probe tack test shown in Fig. 2 on 11 types of label samples made using the first to fourth adhesives and a commercially available adhesive, measured the peak value PV of the probe tack value, and measured the deformation time T, and calculated an index value by dividing the deformation time T by the peak value PV of the probe tack value. In addition, the peeling sound of the 11 types of label samples was measured, and the relationship between the index value and the peeling sound was examined.
[0075] Regarding the peeling noise, a label sample measuring 25mm wide x 75mm long was attached to a PET film used as a film packaging material with a 2kg roller, and after 5 seconds it was peeled off at a speed of 20m / min. The volume of the crackling sound was measured with a sound level meter and the sound was also rated by hearing on a three-level scale: good, fair, or bad.
[0076] The sound level was measured using a data logger sound level meter SL-1373SD (manufactured by Custom Co., Ltd.) in a quiet office room with a noise level of 48 dB, with the sound level meter placed 5 cm away from the adherend.
[0077] The evaluation criteria for the peeling sound based on hearing, ◯, △, ×, are as follows:
[0078] ○: No crispy sound △: Low crispiness ×: Crisp sound The adhesive composition of each sample, the results of the probe tack test, and the results of the peel sound are shown in Tables 4 and 5 below. Because the tables are large, they are divided into Tables 4 and 5, but they are actually one table, and Samples No. 1 to No. 11 in Table 4 correspond to Samples No. 1 to No. 11 in Table 5.
[0079] [Table 4]
[0080] [Table 5] Since the peak probe tack value PV and deformation time T measured in the probe tack test vary as described above, the index value, ie, deformation time / peak probe tack value (T / PV), also varies.
[0081] For this reason, six test pieces were prepared for each of the labels using the adhesives of Samples No. 1 to No. 11, and a probe tack test was performed with the number of measurements N=6.
[0082] Table 4 shows each sample number, the adhesive composition, the peak value PV (g / 5mmφ) for the number of measurements N=6 (1 to 6) in the probe tack test, and each deformation time T (ms).
[0083] Table 5 shows the results of each index value, i.e., deformation time / peak value (T / PV) and peeling sound, calculated using each sample No. that is the same as Table 4, each peak value PV and each deformation time T for the measurement number N=6 (1 to 6) shown in Table 4.
[0084] In order to eliminate the effects of variation, among the index values shown in Table 5 calculated using each peak value PV and each deformation time T for the measurement number N = 6 (1 to 6), the maximum index value and the minimum index value are excluded as "Exclusion 1" and "Exclusion 2", respectively, and the average of the remaining index values for the measurement number N = 4 is used as the final index value.
[0085] The values in the columns "Exclusion 1" and "Exclusion 2" in Table 5 are values calculated using the values in the columns "5" and "6" of the peak value PV and deformation time T in Table 4, respectively.
[0086] For example, the index value "0.081" in the "Exclusion 1" column for sample No. 1 in Table 5 is obtained by dividing the measurement value "77.0" in the "5" column for deformation time of sample No. 1 in Table 4 by the measurement value "951" in the "5" column for peak value. Similarly, the index value "0.096" in the "Exclusion 2" column for sample No. 1 in Table 5 is obtained by dividing the measurement value "75.5" in the "6" column for deformation time of sample No. 1 in Table 4 by the measurement value "785" in the "6" column for peak value.
[0087] In Table 4, the adhesive composition is shown as a mass ratio when the mass of the adhesive is taken as "100".
[0088] As shown in Table 4, samples No. 1 to No. 6 are pressure-sensitive adhesives that include at least one of a first pressure-sensitive adhesive and a second pressure-sensitive adhesive.
[0089] Sample No. 1 is an adhesive containing only the first adhesive, and sample No. 6 is an adhesive containing only the second adhesive.
[0090] The adhesives of Samples No. 2 to No. 5 are adhesives obtained by blending a first adhesive with a second adhesive. The mass ratio of the first adhesive to the second adhesive is 50:50 in Sample No. 2, 30:70 in Sample No. 3, 15:85 in Sample No. 4, and 10:90 in Sample No. 5.
[0091] Samples No. 7 to No. 10 are pressure-sensitive adhesives that include at least one of the third pressure-sensitive adhesive and the fourth pressure-sensitive adhesive.
[0092] Sample No. 7 is an adhesive containing only the third adhesive, and sample No. 8 is an adhesive containing only the fourth adhesive.
[0093] The adhesive of samples No. 9 and No. 10 is an adhesive blend of the third adhesive and the fourth adhesive. The mass ratio of the third adhesive to the fourth adhesive is 15:85 in sample No. 9 and 85:15 in sample No. 10.
[0094] Sample No. 11 is a sample using the above commercially available adhesive.
[0095] Of samples No. 1 to No. 6 which used the first adhesive and the second adhesive, samples No. 1 and No. 2 had average index values of "0.086" and "0.084", as shown in Table 5. The peeling sound of samples No. 1 and No. 2 was evaluated by ear as "X" in both cases, with a loud crunching sound, and the peeling sounds measured with a sound level meter were 76 dB and 81 dB.
[0096] Samples No. 7 to No. 10, which used the third and fourth adhesives, had average index values of "0.087", "0.061", "0.063", and "0.078", as shown in Table 5. The peeling sound of these samples No. 7 to No. 10 was all rated x by ear, meaning that the crunching sound was loud, and the peeling sounds measured with a sound level meter were 79 dB, 77 dB, 78 dB, and 77 dB.
[0097] In this way, for samples No. 1, No. 2, and No. 7 to No. 10, whose average index value was lower than the "0.087" of sample No. 7, the peeling sound was all rated as "X" by ear, meaning that the crunching sound was loud, and the peeling sounds measured with a sound level meter were all 76 dB or higher, meaning that the peeling sounds were loud.
[0098] In contrast, among samples No. 1 to No. 6 which used the first adhesive and the second adhesive, sample No. 3 had an average index value of "0.099" as shown in Table 5. The peeling sound of sample No. 3 was evaluated by hearing as △, with a small crunching sound and a peeling sound measured with a sound level meter of 55 dB.
[0099] Furthermore, among samples No. 1 to No. 6 which used the first adhesive and the second adhesive, samples No. 4 to No. 6 had average index values of "0.101," "0.106," and "0.116," as shown in Table 5. The peeling sound of samples No. 4 to No. 6 was evaluated by ear as ◯, with no crackling sound, and the peeling sound measured with a sound level meter was all 48 dB.
[0100] For sample No. 11, which used a commercially available adhesive, the average index value was "0.124" as shown in Table 5. The peeling sound of sample No. 11 was evaluated by hearing as "good" with no crackling sound, and the peeling sound measured with a sound level meter was 48 dB.
[0101] In the case of samples No. 3 to No. 6 and No. 11, whose average index value was 0.099 or more, the peeling sound was evaluated by hearing as △ or ◯, meaning that the crunching sound was small or absent, and the peeling sound measured by a sound level meter was 55 dB or less in all cases.
[0102] FIG. 3 is a diagram showing the relationship between the average index values (deformation time / peak value) of Samples No. 1 to No. 11 and the peeling noise measured with a sound level meter.
[0103] As shown in FIG. 3, the samples can be divided into a group consisting of samples Nos. 1, 2, 7 to 10, in which the average index value is equal to or less than "0.087" for sample No. 7 and the peeling noise exceeds 70 dB, and a group consisting of samples Nos. 3 to 6 and 11, in which the average index value is equal to or more than "0.099" for sample No. 3 and the peeling noise is less than 60 dB.
[0104] In this way, the samples can be divided into a group of samples with large peeling noise and a group of samples with small peeling noise based on the average index value.
[0105] As shown in FIG. 3 and Table 5, in order to reduce the peeling noise, the average index value is preferably equal to or greater than the average index value of sample No. 3, which is "0.099."
[0106] The samples with an average value of this index of 0.099 or more, excluding sample No. 11 which used a commercially available adhesive, were sample Nos. 3 to 6, which were samples which used the first and second adhesives.
[0107] The present inventors have studied the change over time in adhesive strength of the adhesive. In studying the change over time in adhesive strength of the adhesive, the first and second adhesives, which were effective in reducing peeling noise as described above, were used. Using these first and second adhesives, 20 types of sample labels, sample No. 1 to No. 20, were produced. The size of the samples was 25 mm wide x 5 mm long.
[0108] The substrate was a 50 μm thick PET film. A sample label was also made using the same commercially available adhesive as in the probe tack test, and designated as Sample No. 21. The substrate for the label sample using this commercially available adhesive was also a 50 μm thick PET film.
[0109] The adhesive strength was measured by attaching each sample label to PET packaging material with a 2 kg roller, and measuring the adhesive strength after 30 minutes at 23°C and 50% RH in accordance with JIS Z0237 at a peel speed of 300 mm / min and a peel angle of 180°.
[0110] This measured value of adhesive strength was set as "100" which is the standard (blank) for calculating the rate of change in adhesive strength.
[0111] In addition, the labels of each sample were attached to PET packaging material, and the samples were stored under each accelerated environment, specifically, for 7 days under dry conditions at 40°C, 7 days under conditions of 40°C and 90% RH, 7 days under dry conditions at 70°C, and 7 days under conditions of 60°C and 90% RH. After adjusting the humidity of each sample stored under each accelerated environment to 23°C and 50% RH, the adhesive strength was measured.
[0112] The peeling sound when peeling off the tape immediately after application was evaluated by hearing. The peeling speed was set to a relatively fast speed of about 30 cm / sec. The hearing evaluation was rated on a four-point scale according to the following evaluation criteria.
[0113] ○: No crispy sound ○△: Slightly crispy sound △: Low crispiness ×: Crisp sound The preferred peeling sounds are ○, △, or ◯.
[0114] Table 6 below shows the sample configurations, the measurement results of adhesive strength, and the evaluation results of peeling noise.
[0115] [Table 6] Table 6 shows the sample number, the composition of the sample including the adhesive compound, the blank adhesive strength (N / 10 mm) used as the basis for calculating the rate of change in adhesive strength, the rate of change in adhesive strength (%) after storage in each accelerated environment, and the evaluation results of the peeling sound. Like Table 4 above, Table 6 shows the mass ratio of the first and second adhesives, and the mass ratio of the curing agent when the mass of the adhesive is "100".
[0116] Sample No. 1 is an adhesive containing only the first adhesive, while Samples No. 2 to No. 4 have mass ratios of the first adhesive to the second adhesive of 80:20, 70:30, and 50:50, decreasing the mass ratio of the first adhesive and increasing the mass ratio of the second adhesive. Samples No. 1 to No. 4 each contain a curing agent in a mass ratio of "1".
[0117] In samples No. 5 to No. 7, the mass ratio of the first adhesive to the second adhesive was all 30:70, and the amounts of curing agent added were "1," "1.5," and "2" in mass ratio.
[0118] In samples No. 8 to No. 12, the mass ratio of the first adhesive to the second adhesive was all 20:80, and the amounts of curing agent added were, in mass ratios, "1," "1.2," "1.3," "1.5," and "2."
[0119] In samples No. 13 to No. 16, the mass ratio of the first adhesive to the second adhesive was all 15:85, and the amounts of curing agent added were, in mass ratio, "1," "1.2," "1.3," and "1.5."
[0120] In both samples No. 17 and No. 18, the mass ratio of the first adhesive to the second adhesive was 10:90, and the amounts of the curing agent added were set to mass ratios of "1" and "1.2."
[0121] Samples No. 19 and No. 20 are adhesives containing only the second adhesive, and the amounts of curing agent added are set to "1" and "1.2" in mass ratio.
[0122] As described above, the label of each sample was attached to the packaging material, and the adhesive strength measured after 30 minutes at 23°C and 50% RH was set as "100", which is the standard (blank) for calculating the rate of change.
[0123] In addition, the labels of each sample were attached to PET packaging material and stored under each accelerated environment. After storage, the adhesive strength of the labels of each sample was measured and the rate of change (%) was calculated.
[0124] In sample No. 1, which was the first adhesive alone, the rate of change after storage for 7 days under conditions of 40° C. and 90% RH increased the most, reaching 129(%).
[0125] In sample No. 2, in which the mass ratio of the first adhesive to the second adhesive was 80:20, the rate of change after storage for 7 days under conditions of 40° C. and 90% RH increased the most, reaching 117(%).
[0126] Sample No. 3, in which the mass ratio of the first adhesive to the second adhesive was 70:30, showed the highest rate of change after storage for 7 days under conditions of 40° C. and 90% RH, reaching 113(%).
[0127] Sample No. 4, in which the mass ratio of the first adhesive to the second adhesive was 50:50, showed the highest rate of change after storage for 7 days under conditions of 60° C. and 90% RH, reaching 124(%).
[0128] In addition, samples No. 5, No. 6, and No. 7, in which the mass ratio of the first adhesive to the second adhesive was 30:70, showed the highest rate of change after storage for 7 days under conditions of 60°C and 90% RH, which were 141%, 139%, and 156%, respectively.
[0129] Among samples No. 8 to No. 12, in which the mass ratio of the first adhesive to the second adhesive was 20:80, No. 8, No. 9, No. 10, and No. 11 all showed the greatest increase in the rate of change after storage for 7 days under conditions of 60°C and 90% RH, at 142(%), 146(%), 139(%), and 143(%), respectively. Sample No. 12 showed the greatest increase in the rate of change after storage for 7 days under dry conditions at 70°C, at 133(%).
[0130] Samples No. 13, No. 14, No. 15, and No. 16, in which the mass ratio of the first adhesive to the second adhesive was 15:85, all showed the greatest increase in rate of change after storage for 7 days under conditions of 60°C and 90% RH, which were 160(%), 159(%), 162(%), and 142(%), respectively.
[0131] In samples No. 17 and No. 18, in which the mass ratio of the first adhesive to the second adhesive was 10:90, the rate of change after storage for 7 days under conditions of 60°C and 90% RH increased the most, to 144% and 168%, respectively.
[0132] Thus, in Samples No. 1 to No. 18, the highest rate of change was less than 200(%), which was favorable.
[0133] In contrast, sample No. 19, which contained only the second adhesive, showed the highest rate of change after storage for 7 days under conditions of 60°C and 90% RH, at 375% and 474%, respectively. Thus, in samples No. 19 and 20, which contained only the second adhesive, the highest rate of change was significantly higher than 200%, and it was not possible to suppress the increase in adhesive strength over time.
[0134] Sample No. 21, which used a commercially available adhesive from another manufacturer, showed the highest rate of change after storage for 7 days under conditions of 60°C and 90% RH, at 242%.
[0135] From the results shown in Table 6 above, in order to suppress the increase in adhesive strength over time, the adhesives of samples No. 1 to No. 18, in which the highest rate of change was less than 200(%), are preferred. That is, it is preferred to gradually decrease the proportion of the first adhesive from the first adhesive alone and gradually increase the proportion of the second adhesive, so that the mass ratios of the first adhesive to the second adhesive are 80:20, 70:30, 50:50, 30:70, 20:80, 15:85, and 10:90.
[0136] In samples No. 19 and No. 20, which contained only the second adhesive, the highest rate of change was significantly higher than 300(%), and the increase in adhesive strength over time could not be suppressed.
[0137] Of samples No. 1 to No. 18 in Table 6, which are preferable for suppressing an increase in adhesive strength over time, the adhesives used in samples No. 1, No. 4, No. 5, No. 13, and No. 17 are the same as the adhesives used in samples No. 1, No. 2, No. 3, No. 4, and No. 5 in Tables 3 and 4 above.
[0138] Moreover, the adhesive of sample No. 19, which cannot suppress the increase in adhesive strength over time, is the same as the adhesive of sample No. 6 in Tables 4 and 5, that is, an adhesive containing only the second adhesive.
[0139] Therefore, in order to suppress the increase in adhesive strength over time, the preferred adhesives are the adhesives of samples No. 1 to No. 5 in Tables 4 and 5, and the adhesive that cannot suppress the increase in adhesive strength over time is the adhesive of sample No. 6 in Tables 4 and 5.
[0140] As shown in Table 5, the average index values of samples No. 1 to No. 5, which are pressure-sensitive adhesives that are preferable for suppressing an increase in adhesive strength over time, are "0.086," "0.084," "0.009," "0.101," and "0.106."
[0141] In contrast, the average index value of sample No. 6, which is an adhesive that cannot suppress an increase in adhesive strength over time, is "0.116," which is higher than the average index values of all of samples No. 1 to No. 5.
[0142] Therefore, in order to suppress an increase in adhesive strength over time, it is preferable that the average index value of the pressure-sensitive adhesive is equal to or less than the average index value of sample No. 5, which is 0.106.
[0143] In order to reduce the peeling sound as described above, it is preferable that the average index value be equal to or greater than the average index value of sample No. 3, which was "0.099." Therefore, in order to reduce the peeling sound and suppress an increase in adhesive strength over time, it is preferable that the average index value of the adhesive be equal to or greater than "0.099" and equal to or less than "0.106."
[0144] In Table 6, samples No. 5 to No. 20, whose peeling sound was evaluated by ear as △ (low crunching sound), ○△ (slight crunching sound), and ○ (no crunching sound), had low peeling sound and were good. Among these samples No. 5 to No. 20, the adhesives of samples No. 5, No. 13, No. 17, and No. 19 are the same as the adhesives of samples No. 3, No. 4, No. 5, and No. 6 in Tables 4 and 5. The average index values of these samples No. 3, No. 4, No. 5, and No. 6 are "0.099", "0.101", "0.106", and "0.116", and all of them have an average index value of "0.099" or more.
[0145] When used as a flap label to open and close the opening of a packaging material, the label is repeatedly attached and opened, and therefore requires re-openability.
[0146] Therefore, a re-opening test was conducted by repeatedly sticking and peeling the labels of sample No. 4 in Tables 4 and 5 above, i.e., sample No. 4 in which the mass ratio of the first adhesive to the second adhesive is 15:85, and sample No. 11 in which the above-mentioned commercially available adhesive from another company was used.
[0147] In this re-opening test, the label of each sample was attached to the packaging material with a 2 kg roller, and then measurements were made in accordance with JIS Z0237 at a peel speed of 300 mm / min and a peel angle of 180°.
[0148] PET was used as the packaging material, and each sample label was affixed to this packaging material. The first adhesive strength value after 30 minutes at 23°C and 50% RH was set as "100", the standard (blank) for calculating the rate of change.
[0149] The adhesive strength was measured on the 2nd, 50th, and 100th passes, and the rate of change (%) from the 1st pass was calculated. A preferable rate of change is 65% or more on the 100th pass.
[0150] The test results are shown in Table 7 below.
[0151] [Table 7] The label of sample No. 4 and the commercially available label of sample No. 11 in Tables 4 and 5 above all showed a desirable rate of change of 65% or more after the 100th test.
[0152] In the embodiment of the label 1 shown in FIG. 1, the surface substrate 2 has two layers, a substrate film and a laminate layer, but it may be a substrate film only, or may include a printed layer or other layers. [Explanation of symbols]
[0153] 1. Label 2 Surface base material 3 Adhesive layer 4 Release paper 5. Base film 6 Laminate Layer 7. Adhesive 8 Probes
Claims
1. A label having an adhesive layer, In a probe tack test in which a probe tack value is measured when a probe is pressed against an adhesive surface of the pressure-sensitive adhesive layer and then peeled off, the average value of an index value (ms / g) obtained by dividing the time (ms) from the point at which peeling of the probe pressed against the adhesive surface is started to the point at which the probe is peeled off from the adhesive surface by the peak value (g) of the probe tack value is 0.099 or more and 0.106 or less. label.
2. A method for producing a label having a substrate and an adhesive layer, comprising the steps of: A blending step of blending the first adhesive and the second adhesive; a pressure-sensitive adhesive layer forming step of forming a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive blended in the blending step on one surface of the base material, In a probe tack test in which a probe tack value is measured when a probe is pressed against an adhesive surface of the formed adhesive layer and then peeled off, the average value of an index value (ms / g) obtained by dividing the time (ms) from the start of peeling the probe pressed against the adhesive surface to the time the probe is peeled off by the peak value (g) of the probe tack value is 0.099 or more and 0.106 or less. How the labels are manufactured.
3. The first pressure-sensitive adhesive has an average index value of less than 0.099 in the probe tack test of a first pressure-sensitive adhesive layer made of the first pressure-sensitive adhesive, and the second pressure-sensitive adhesive has an average index value of more than 0.106 in the probe tack test of a second pressure-sensitive adhesive layer made of the second pressure-sensitive adhesive. A method for producing the label according to claim 2.
4. In the blending step, the first adhesive and the second adhesive are blended to have a mass ratio of 30:70 to 10:
90. A method for producing the label according to claim 2 or 3.
5. The first adhesive has an adhesive strength of 1.52 to 1.78 (N / 10 mm), a holding strength of 0 to 0.02 mm after 1440 minutes (24 hours), and a ball tack of No. 12 to 14; The second adhesive has an adhesive strength of 0.64 to 0.79 (N / 10 mm), a holding strength of 0.02 to 0.06 mm after 1440 minutes (24 hours), and a ball tack of No. 12 to 14. A method for producing the label according to claim 4.
Citation Information
Patent Citations
Absorbent article
JP2006055268A